(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the frequency of femoral ante version in patients presenting with Developmental Dysplasia of Hip (DDH). Methods: This Cross-sectional was conducted in Ghurki Trust Teaching Hospital, Lahore from April 2019 to September 2019.All children of DDH fulfilling the inclusion criteria were subjected to Craig test for the evaluation of femoral anteversion. An angle more than 15° (normal 8-15°) was termed as femoral anteversion (internal torsion). Results: In our study total 57 children with mean age 5 years± 3.26 were included. Male children were 33 (58%) and female 24 (42%). The frequency of femoral anteversion was detected in 30(52%) children with DDH. Conclusion: Femoral anteversion was found in most of children suffering from developmental dysplasia of hip. All children with DDH must be screened for femoral anteversion and the operating surgeon must plain to correct this deformity precisely while operating on patients with DDH.